The Potential of Microwave Assisted Hydrodistillation in Extraction of Essential Oil from Cinnamomum Cassia (cinnamon) - Nitthiyah, Jeyaratnam; Nour, A. H.; Akindoyo, John Olabode (Asian Research Publishing Network (ARPN), 2016)
In this research, Microwave Assisted Hydrodistillation (MAHD) was used to extract essential oil from Cinnamomum Cassia (cinnamon). The effect of different parameters, such as water to raw material ratio (6:1, 8:1 & 10:1), microwave power (200 W, 225 W & 250 W) and extraction time (30 min, 60 min, 90 min, 120 min & 150 min) on the extraction yield and its major constituents were investigated. The essential oil was analysed by gas chromatography/ mass spectrometric (GC-MS) to evaluate the effect of extraction method on the content of its main constituent which was trans-Cinnamaldehyde. The optimum condition was found at water to raw material ratio of 8:1, microwave power of 250 W and extraction time of 90 min and the yield obtained under this condition was about 2.55%. The result obtained from GC-MS analysis revealed that the use of microwave irradiation did not adversely influence the composition of the essential oil. The main constituents found through MAHD was more desirable in terms of quality and quantity when compared to the conventional methods. The results obtained herein suggest that MAHD method could serve as a suitable and effective method for the extraction of essential oil from Cinnamomum Cassia (cinnamon).